If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4psquared + -12p + 7 = 0 Reorder the terms: 7 + 4adepqrsu + -12p = 0 Solving 7 + 4adepqrsu + -12p = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + 4adepqrsu + -7 + -12p = 0 + -7 Reorder the terms: 7 + -7 + 4adepqrsu + -12p = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 4adepqrsu + -12p = 0 + -7 4adepqrsu + -12p = 0 + -7 Combine like terms: 0 + -7 = -7 4adepqrsu + -12p = -7 Add '12p' to each side of the equation. 4adepqrsu + -12p + 12p = -7 + 12p Combine like terms: -12p + 12p = 0 4adepqrsu + 0 = -7 + 12p 4adepqrsu = -7 + 12p Divide each side by '4depqrsu'. a = -1.75d-1e-1p-1q-1r-1s-1u-1 + 3d-1e-1q-1r-1s-1u-1 Simplifying a = -1.75d-1e-1p-1q-1r-1s-1u-1 + 3d-1e-1q-1r-1s-1u-1
| 45logx=3 | | 10X+36=6X+20 | | 34-9k=88 | | -5X-40=-3X-26 | | 2x^2-25x+80=0 | | -(3w+4)+5(w-2)-3(6w-8)=1 | | (x+35)=(3x+5) | | 10x^2+9x-117=0 | | 3x+8=4x-10 | | 10x^2+9x-108=0 | | -2x^2+54x=0 | | 6(y-6)/10(y-6) | | H(5x)=3x^2+2 | | 2x^2+52x=0 | | 25x+16y=287.28 | | 2x^2+18x+162=0 | | -2(2x-4x)=6+18 | | 4=2k+22 | | (9y^2-8y+8)-(3y^2-8y+2)= | | -8b+3+6b=3b+8 | | x*1.618=60 | | 5y-8=-28 | | Y^2+18y+69=0 | | 28+9=2n | | 4x/5x-10=35 | | (3.99)2x+19.99y=111.88 | | 2r+12=6 | | -16t^2+25t+10= | | (4x^3-6x+7)=(-19x^3-15x-18) | | -16t^2+25t+8= | | 25x^2+75x-3250=0 | | 18x+94=10x+54 |